Desain dan Implementasi Mobile Augmented Reality Untuk Media Pembelajaran 3D Hidrosfer - Ryan Aristo; Tri Afirianto; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Geography lessons are an impossible lesson for most students. In this case the role of information technology such as mobile augmented reality technology is to provide information on hydrosphere information. Based on this poverty, knowledge of the environment and hydrosphere is indeed quite difficult to explain because these two things are natural examples that are difficult for people to see. This natural knowledge and hydrosation is usually obtained from books, teaching staff or science experts. To overcome by adding knowledge as 3D hydrosphere learning media through Augmented Reality system in the form of mobile augmented reality application for 3D hydrosphere learning media. Based on all functional requirements, validation testing has fulfilled. On the results using the Usability Scale System method of usability testing obtained SUS score of 82. The SUS score shows that the mobile augmented reality application for 3D hydrosphere learning media can easily be done. The results of media testing for mobile augmented reality applications for 3D hydrosphere learning media can be used well for users.